miR-370 mimic inhibits replication of Japanese encephalitis virus in glioblastoma cells - Li W (Dove Medical Press, 2016)
Wenjuan Li,1 Peng Cheng,2 Shangdan Nie,1 Wen Cui1 1School of Forensic and Laboratory Medicine, Jining Medical University, 2Shandong Academy of Medical Sciences, Shandong Institute of Parasitic Diseases, Jining, People’s Republic of China Abstract: Japanese encephalitis (JE) is one of the most severe viral infections of the central nervous system. No effective treatment for JE currently exists, because its pathogenesis remains largely unknown. The present study was designed to screen the potential microRNAs (miRNAs) involved in JE. Glioblastoma cells were collected, after being infected with the Japanese encephalitis virus (JEV). Total miRNAs were extracted and analyzed using an miRNA chip. One of the most severely affected miRNAs was selected, and the role of miR-370 in JEV infection was investigated. Cell viability and apoptosis of the host cells were evaluated. JEV replication was detected via analysis of gene E expression. Real-time polymerase chain reaction was used to determine the levels of endogenous miR-370 and expression of innate immunity-related genes. Following JEV infection, 114 miRNAs were affected, as evidenced by the miRNA chip. Among them, 30 miRNAs were upregulated and 84 were downregulated. The changes observed in five miRNAs were confirmed by real-time polymerase chain reaction. One of the significantly downregulated miRNAs was miR-370. Therefore, miR-370 mimic was transfected into the cells, following which the levels of endogenous miR-370 were significantly elevated. Concurrently, JEV replication was significantly reduced 24 hours after transfection of miR-370 mimic. Functionally, miR-370 mimic mitigated both JEV-induced apoptosis and the inhibition of host cell proliferation. Following JEV infection, interferon-β and nuclear factor-kappa B were upregulated, whereas miR-370 mimic prevented the upregulation of the genes induced by JEV infection. The present study demonstrated that miR-370 expression in host cells is downregulated following JEV infection, which further mediates innate immunity-related gene expression. Taken together, miR-370 mimic might be useful to prevent viral replication and infection-induced host cell injury. Keywords: miR-370, Japanese encephalitis, glioblastoma cells, NF-κB